2004
DOI: 10.1242/jeb.01222
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in cardiorespiratory patterns associated with terrestrial apnoeas in harbour seal pups

Abstract: During the nursing period seals undergo several physiological and behavioural changes. A key component of development is increased cardiorespiratory control, fundamental for breath-holding and thus diving. This study focused on the ontogenetic changes in cardiac responses to respiration in quietly resting, pre-weaned harbour seal pups (Phoca vitulina). During periods of quiet rest, breathing became episodic, eupnoea interspersed with periods of apnoea. Little change was observed in respiration (~35·breaths·min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Compared to the efficient dive response in adults; however, pinniped neonates have higher mass-specific metabolic rates due to their smaller size, faster growth rate, and relatively poor cardiovascular control (Miller and Irving 1975;Castellini et al 1994;Donohue et al 2000;Lapierre et al 2004), which in combination with lower TBO 2 stores reduces the animal's breath-hold capacity, or aerobic dive limit (ADL). As O 2 stores are depleted, anaerobic respiration begins to predominate, and lactate accumulates in tissues and blood, requiring more extensive post dive recovery periods at the surface after dives (Kooyman et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the efficient dive response in adults; however, pinniped neonates have higher mass-specific metabolic rates due to their smaller size, faster growth rate, and relatively poor cardiovascular control (Miller and Irving 1975;Castellini et al 1994;Donohue et al 2000;Lapierre et al 2004), which in combination with lower TBO 2 stores reduces the animal's breath-hold capacity, or aerobic dive limit (ADL). As O 2 stores are depleted, anaerobic respiration begins to predominate, and lactate accumulates in tissues and blood, requiring more extensive post dive recovery periods at the surface after dives (Kooyman et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…2), whereas in previous studies, it was observed only in pups of harbor seal (Phoca vitulina), whose heart rate control has not fully been developed yet (Lapierre et al 2004). Vagal control is considered to be important to maintain lower heart rate during rest-associated apnea (Lapierre et al 2004). We presume that this control may be lessened in the seal on partial alert, possibly due to motions or sounds created by the observers.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, bimodal distribution of apneic heart rate was documented for the Wrst time in an adult seal (Fig. 2), whereas in previous studies, it was observed only in pups of harbor seal (Phoca vitulina), whose heart rate control has not fully been developed yet (Lapierre et al 2004). Vagal control is considered to be important to maintain lower heart rate during rest-associated apnea (Lapierre et al 2004).…”
Section: Discussionmentioning
confidence: 86%
“…Previous work has demonstrated that young marine mammals have much lower endogenous O 2 stores than adults, primarily because of significantly lower myoglobin stores in their muscles (Noren et al 2001;Richmond et al 2006;Burns et al 2007;Lestyk et al 2009;Prewitt et al 2010). In addition, because neonates have high metabolic rates and lack the ability to reduce their heart rate or vasoconstrict (Castellini et al 1994;Lapierre et al 2004;Greaves et al 2005), their small tissue O 2 stores will be exhausted quickly, even though absolute enzyme activities are higher than in adults. Unfortunately, should this occur, the lower absolute and metabolically scaled LDH P→L activity indicate that muscles would be unable to sustain prolonged periods anaerobic energy production, while lower buffering capacity (Lestyk et al 2009) and LDH L→P activity suggest that metabolic perturbations that accompany anaerobiosis would persist for longer periods of time than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to adults, in which the physiological and biochemical adaptations to support underwater activity are well developed, seal pups have tissue O 2 stores ∼50% below adult values, have mass-specific resting metabolic rates four to six times higher than adults, and lack the cardiovascular control necessary for bradycardia and vasoconstriction during diving (Lavigne et al 1986;Worthy and Lavigne 1987;Lydersen et al 1997;Lapierre et al 2004;Burns et al 2004Burns et al , 2007Greaves et al 2005). In addition, the notable variation in [Mb] that exists among different skeletal muscles in adults is absent in young pups (Richmond et al 2006;Lestyk et al 2009;Shero et al 2012;Geiseler et al 2013).…”
Section: Introductionmentioning
confidence: 99%